To examine the spectrum of bowel wall thickening on computed tomography (CT) scans and to provide an academic interpretation of these findings - Reddy, K Vishnuvardhan; Reddy, Chintala Bharath (Asian Journal of Medical Radiological Research, 2022)
Background: Computed tomography (CT) is a highly effective noninvasive modality for the assessment of bowel wall thickening. Aim: The objective of this study is to examine the spectrum of bowel wall thickening on computed tomography (CT) scans and to provide an academic interpretation of these findings. Subjects and Methods: The research was a prospective study carried out within the department of radiology at Dhanalakshmi Srinivasan Medical College and Hospital. Inclusion criteria encompassed patients who had a documented medical history of subacute or chronic bowel obstruction. This study included patients who exhibited clinical manifestations indicative of bowel disease, such as hematemesis, melena, or rectal bleeding. Inclusion criteria encompassed patients who had a documented medical history of subacute or chronic bowel obstruction. 70 subjects were chosen for the study without considering their age or gender, from both inpatient and outpatient department. A computed tomography (CT) examination will be conducted using a 64-slice spiral CT machine. Results: A total of 50 cases (71.43%) were identified as proven malignant bowel wall lesions, while 20 cases (28.57%) were diagnosed as benign instances of bowel wall thickening. In the present study, it was observed that the identification of pronounced, asymmetrical, localized, and varied thickening of the bowel wall yielded sensitivity values of 61.58%, 79.15%, 91.47%, and 55.39% respectively. Furthermore, the specificity values for the aforementioned characteristics were determined to be 89.74%, 77.11%, 83.41%, and 89.14% respectively, in relation to the detection of malignant etiologies associated with bowel wall thickening. Conclusion: It is concluded that computed tomography (CT) features and enhancement patterns exhibit a high level of sensitivity and specificity in distinguishing between benign and malignant bowel wall thickening.